2015
DOI: 10.3390/ijms161023300
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Photodynamic Therapy as a Possible Therapeutic Alternative in the Treatment of Basal Cell Carcinoma

Abstract: Basal cell carcinoma (BCC) is the most common cancer in individuals with fair skin type (I–II) and steadily increasing in incidence (70% of skin malignancy). It is locally invasive but metastasis is usually very rare, with an estimated incidence of 0.0028%–0.55%. Conventional therapy is surgery, especially for the H region of the face and infiltrative lesions; in case of inoperable tumors, radiotherapy is a valid option. Recently, topical photodynamic therapy (PDT) has become an effective treatment in the mana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 99 publications
0
23
1
3
Order By: Relevance
“…However, other studies found no association between lesion location and response . Tumour thickness (which we did not examine) has been shown to predict response to PDT …”
Section: Factors Predicting Clinical Clearance At 3‐month Review and contrasting
confidence: 70%
See 2 more Smart Citations
“…However, other studies found no association between lesion location and response . Tumour thickness (which we did not examine) has been shown to predict response to PDT …”
Section: Factors Predicting Clinical Clearance At 3‐month Review and contrasting
confidence: 70%
“…There is little evidence available on the impact of patient, lesion and treatment characteristics on the effectiveness of therapy. Studies examining PDT failure rates have had conflicting results . In our centre, PDT is the therapeutic preference for precancerous lesions and superficial skin cancers < 1 mm thick on poorly healing body sites, e.g.…”
Section: Factors Predicting Clinical Clearance At 3‐month Review and mentioning
confidence: 96%
See 1 more Smart Citation
“…Традиционно считается, что ФДТ может быть эффективна только при лечении опухолей небольшого размера, но в клиниче-ской практике нередко встречаются не только первичные, но и рецидивные местно-распространенные новообразования, при которых выбор эффективного метода лечения, в частности ФДТ, является предметом дискуссий в отечественной и зарубежной ли-тературе [9][10][11][12][13].…”
Section: краткие сообщения и заметки из практикиunclassified
“…В результате фотохимической реакции происходит генерация синглетного кислорода внутри клеток и образование свободных радикалов, повреждающих мембраны и органеллы клеток, наиболее интенсивно накопивших ФС, вызывая их ги-бель по механизму некроза и апоптоза [7,8]. Селективность на-копления ФС обеспечивает избирательность повреждения опу-холи и минимальное поражение здоровых тканей при проведе-нии лазерного облучения [7].Традиционно считается, что ФДТ может быть эффективна только при лечении опухолей небольшого размера, но в клиниче-ской практике нередко встречаются не только первичные, но и рецидивные местно-распространенные новообразования, при которых выбор эффективного метода лечения, в частности ФДТ, является предметом дискуссий в отечественной и зарубежной ли-тературе [9][10][11][12][13].В отделе фотодинамической диагностики и терапии МРНЦ им. А.Ф.…”
unclassified